2018
DOI: 10.1177/0963689718806818
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA in Acute Ischemic Stroke: Mechanisms, Biomarkers and Therapeutic Targets

Abstract: Non-coding RNAs (ncRNAs) are a class of functional RNAs that regulate gene expression in a post-transcriptional manner. NcRNAs include microRNAs, long non-coding RNAs and circular RNAs. They are highly expressed in the brain and are involved in the regulation of physiological and pathophysiological processes, including cerebral ischemic injury, neurodegeneration, neural development, and plasticity. Stroke is one of the leading causes of death and physical disability worldwide. Acute ischemic stroke (AIS) occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 121 publications
1
81
0
Order By: Relevance
“…CircRNAs have multiple regulatory functions and mechanisms that modify transcriptional and post-transcriptional regulation 7,8 . For posttranscriptional regulation, circRNAs can act as microRNA (miRNA) sponges or competitively combine with miRNA 9 . Cir-cRNAs play critical roles in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs have multiple regulatory functions and mechanisms that modify transcriptional and post-transcriptional regulation 7,8 . For posttranscriptional regulation, circRNAs can act as microRNA (miRNA) sponges or competitively combine with miRNA 9 . Cir-cRNAs play critical roles in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs are a class of non‐coding RNAs that are involved in the development of vascular diseases 5,6 . Circular circTLK1 deteriorated myocardial ischaemia/reperfusion injury via regulating the TNF signalling pathway 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that several miRNAs can dramatically alter normal physiological processes and are involved in the pathogenesis of human diseases [17]. Accumulating evidence has demonstrated that aberrant expression of miRNAs play critical roles in central nervous system injury [18][19][20]. Among the miRNAs, miR-27-3p has been widely studies due to its important role in regulating in ammation and innate immune pathway [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%